SiCN:H thin films deposited by MW‐PECVD with liquid organosilicon precursor: Gas ratio influence versus properties of the deposits. Issue 1 (4th November 2019) - Plujat, Béatrice; Glénat, Hervé; Bousquet, Angélique; Frézet, Lawrence; Hamon, Jonathan; Goullet, Antoine; Tomasella, Éric; Hernandez, Emmanuel; Quoizola, Sébastien; Thomas, Laurent
Abstract: Silicon carbonitride SiCN:H thin films are deposited with microwave plasma‐enhanced chemical vapor deposition. Argon, ammonia, and tetramethylsilane (TMS) (Ar/NH3 /Si(CH3 )4 ) are used for the gas mixture. Plasma gas phase chemistry is studied using optical emission spectroscopy according to the TMS/NH3 gas flow ratio, highlighting the presence of three discharge regimes. Then, the deposited SiCN:H thin films are analyzed by X‐ray photoelectron spectroscopy and energy dispersive X‐ray spectroscopy, enabling us to correlate plasma and film chemistry. Thus, we define three thin film families corresponding to the three discharge regimes occurring in the plasma phase. Properties of these families are studied: Optical properties by spectroscopic ellipsometry, electrical properties by I–V measurements and electron spin resonance, and mechanical properties by nanoindentation and tribology. Abstract : We focus on chemistry correlation between Ar/NH3 /TMS (tetramethylsilane) plasma and SiCN:H thin films as well as final properties of the deposited films. We have used microwave plasma‐enhanced chemical vapor deposition of Ar/NH3 /TMS at 400°C to obtain SiCN:H thin film. Plasma chemistry and final properties of deposited SiCN:H are studied, whether it is physicochemical, optical, electrical, or mechanical properties.